TEKNOLOGI MENDUKUNG SISWA BELAJAR DALAM MATA PELAJARAN ILMU PENGETAHUAN SOSIAL TERINTEGRASI - Tri Nurza Rahmawati (Jurnal Soshum Insentif, 2020)
Absract - This article provides an overview of strategies for using technology to support student learning in integrated Social Science subjects. The learning environment for Social Science subjects can focus on integrating and learning simultaneously for various levels of students. Social Science is a multidisciplinary science in solving problems. This study illustrates four strategies for using technology to support student learning in integrated Social Science among them; a) providing authentic learning contexts, b) offering web-based inquiry environments, c) extending learning through immersive and interactive technology, and d) turning students from recipients into creators. This article also discusses the challenges that are manifested in learning integrated learning environments. This study provides practical implications and research directions for technology-supported learning in an integrated learning environment learning environment. The use of technology in the four strategies identified supports student learning and enhances student experience in ways that are meaningful and support the ideas of students knowing and doing. The study chosen also shows strategies for using technology used to support student learning in different ways. Related Social Sciences Subjects; for example in the discipline of Sociology that examines the problem of poverty that can be discussed with anthropology or culture, geography or the environment and its history. Abstrak- Artikel ini memberikan ulasan mengenai strategi penggunaan teknologi untuk mendukung pembelajaran siswa pada mata pelajaran Ilmu Pengatahuan Sosial yang terintegrasi. Lingkungan belajar mata pelajaran Ilmu Pengatahuan Sosial dapat fokus pada pengintegrasian dan pembelajaran secara bersamaan untuk berbagai tingkatan pelajar. Ilmu Pengatahuan Sosial merupakan Ilmu pengetahuan multidisiplin dalam memecahkan masalah. Studi ini menggambarkan empat strategi penggunaan teknologi untuk mendukung pembelajaran siswa dalam Ilmu Pengatahuan Sosial terintegrasi diantarnya; a) menyediakan konteks pembelajaran otentik, b) menawarkan web-lingkungan penyelidikan berbasis, c) memperluas pembelajaran melalui imersif dan teknologi interaktif, dan d) mengubah siswa dari penerima menjadi pencipta. Artikel ini juga membahas tantangan yang terwujud dalam pembelajaran lingkungan belajar terintegrasi. Studi ini memberikan implikasi praktis dan arahan penelitian untuk pembelajaran yang didukung teknologi dalam lingkungan belajar lingkungan belajar yang terintegrasi. Penggunaan teknologi dalam empat strategi yang diidentifikasi mendukung pembelajaran siswa dan meningkatkan pengalaman siswa dengan cara yang bermakna dan mendukung gagasan siswa mengetahui dan melakukan. Studi yang dipilih juga menunjukkan strategi penggunaan teknologi yang digunakan untuk mendukung pembelajaran siswa dengan cara yang berbeda. Subjek Ilmu Pengetahuan Sosial yang terkait; misalnya pada disiplin ilmu Sosiologi yang mengkaji masalah kemisikinan yang dapat dibahas dengan mata pelajaran antropologi atau budaya, geografi atau lingkungan serta sejarahnya.